Upaya Meningkatkan Minat Belajar Matematika Melalui Media Pembelajaran Berbantuan Komputer - Dewi, Yuliar Astuti (Universitas Islam Negeri Raden Intan Lampung, 2019)
This study aims to increase interest in learning mathematics and describe the process of learning mathematics through computer learning media with the MS Power Point program. The research method used is a quasi-experimental method of classroom action research using the PAOR procedure. The results showed that based on the data shown by the results of the questionnaire, interview or observation during the learning process took place, the average results of the questionnaire interest in learning before the action was 62.17%, after the first cycle was 69.70% and after the second cycle was 76, 88% (high) means there is an increase in interest in learning from pre-study to the first cycle of 7.53% and from the first cycle to the second cycle of 7.18%. For the average results of observations of pre-research learning interest is 38.44% in the first cycle is 52.40% and the second cycle is 70.11% From pre-research to the first cycle there was an increase of 13.96%, from the first cycle to the second cycle up 17.71%. Overall from the pre-study to the end of the study there was an increase of 31.67%. This shows that by using computer-assisted learning media MS Power Point program students become more eager to learn mathematics.